Driving ribosome assembly - Kressler, Dieter; Hurt, Ed; Baßler, Jochen (Biochimica et biophysica acta. Molecular cell research, 2010)
Ribosome biogenesis is a fundamental process that provides cells with the molecular factories for cellular protein production. Accordingly, its misregulation lies at the heart of several hereditary diseases (e.g., Diamond-Blackfan anemia). The process of ribosome assembly comprises the processing and folding of the pre-rRNA and its concomitant assembly with the ribosomal proteins. Eukaryotic ribosome biogenesis relies on a large number (>200) of non-ribosomal factors, which confer directionality and accuracy to this process. Many of these non-ribosomal factors fall into different families of energy-consuming enzymes, notably including ATP-dependent RNA helicases, AAA-ATPases, GTPases, and kinases. Ribosome biogenesis is highly conserved within eukaryotic organisms; however, due to the combination of powerful genetic and biochemical methods, it is best studied in the yeast Saccharomyces cerevisiae. This review summarizes our current knowledge on eukaryotic ribosome assembly, with particular focus on the molecular role of the involved energy-consuming enzymes.